THE IMPLICATIONS OF SPECIAL THEORETICAL KNOWLEDGE AND ITS APPLICATION IN THE PRE-UNIVERISTARY CURRICULUM (GYMNASIUM, 2009)
Special knowledge is represented by the students’ knowledge form the different athletic testsrequired by the pre-universitary curriculum, such as sporting games (volleyball, basketball, football,handball), athletics running, jumping, throwing) and gymnastics (apparatus and floor exercises)..By comparing the acquisition level of the general and special knowledge, there is noticed a moreelevated level in the case of the special knowledge, where students, besides practicing them over PhysicalEducation classes, also find them in mass media or practice them in sports sections, etc.Gymnasium Nr. 1, Anul X, 200969All these impose a new methodological attitude regarding school physical education, especially inthe context of the Olympic Movement.